Human Capital and Performance Management in High Performing Service Industry: A Case of the Impact of an Acquisition - Razi, Nazila; More, Elizabeth (Journal of Accounting, Business and Management (JABM), 2012)
This study examines the impact of a change (namely an acquisition) on the effectiveness of human capital of a High Performance Work System (HPWS) practices in a service setting. It specifically investigates human capital dimensions such as employee incentives, skills, participation, firm-specific knowledge and customer relations performance. This paper builds upon, and goes beyond previous research studies by analysing the impact of acquisition on the association among the variables of an existing model. Results show that acquisition has had no negative impact on the effectiveness of the various components of HPWS practices, such as firm specific knowledge of the employees, customer relations, and overall performance of the organization.